Languages of reform in the eighteenth century: when Europe lost its fear of change - Richter, Susan; Maissen, Thomas; Albertone, Manuela (Routledge, Taylor & Francis Group, 2020)
"Societies perceive "Reform" or "Reforms" as substantial changes and significant breaks which must be well-justified. The Enlightenment brought forth the idea that the future was uncertain and could be shaped by human beings. This gave the concept of reform a new character and new fields of application. Those who sought support for their plans and actions needed to reflect, develop new arguments, and offer new reasons to address an anonymous public. This book aims to compile these changes under the heuristic term of "languages of reform." It analyzes the structures of communication regarding reforms in the 18th century through a wide variety of topics"--
Includes bibliographical references and index
Keywords: Europe -- History -- 18th century; Europe -- Politics and government -- 18th century; Europe -- Social conditions -- 18th century; Europe -- Intellectual life -- 18th century; Aufsatzsammlung; Geschichte 1700-1815; Sprachreform; Sprachwandel; Geistesleben; Politik; Reform; Europa